2017
DOI: 10.1371/journal.pone.0182474
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Leishmania donovani antigen in circulating immune complexes of visceral leishmaniasis subjects for diagnosis

Abstract: The unreliability of most of the existing antibody-based diagnostic kits to discriminate between active and treated VL cases, relapse situation and reinfection are a major hurdle in controlling the cases of Kala-azar in an endemic area. An antigen targeted diagnostic approaches can be an attractive strategy to overcome these problems. Hence, this study was focused on identifying the Leishmania antigens, lies in circulating immune complex (CICs), can be used for diagnostic as well as prognostic purposes. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 53 publications
(58 reference statements)
0
25
0
Order By: Relevance
“…In the present study, a holistic approach has been proposed for the simultaneous elicitation of both T-and B-cells along with the mediation of long-term immunity against VL infection (16,17). The data of the present study establish the vaccine potential of CIC-derived B-cell epitopes and their combination with a potent T-cell epitope to achieve a desirable immune response in the host (3,14). We also explored the possible involvement of ERK-1/2 and p38 MAPK signaling cascade in the observed host immune cell activation.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…In the present study, a holistic approach has been proposed for the simultaneous elicitation of both T-and B-cells along with the mediation of long-term immunity against VL infection (16,17). The data of the present study establish the vaccine potential of CIC-derived B-cell epitopes and their combination with a potent T-cell epitope to achieve a desirable immune response in the host (3,14). We also explored the possible involvement of ERK-1/2 and p38 MAPK signaling cascade in the observed host immune cell activation.…”
Section: Introductionmentioning
confidence: 69%
“…The prevalent circumstances warrant the introduction of potent immune-modulators, which can be used along with a candidate antigen to develop a promising vaccination strategy. Our earlier study revealed the presence of numerous potent Leishmania donovani antigens in the systemic circulation of infected patients (3). Among several identified parasite antigens, the predominant abundance of tubulin folding cofactor D (TFC-D) along with repertoire of its specific antibodies in circulating immune complexes (CICs) suggests its plausible involvement in the activation of parasite-specific B-cell responses (3).…”
Section: Introductionmentioning
confidence: 99%
“…Formation of ICs is a normal part of the immune defense to remove pathogen. More recently, Jamal et al , 2017 [ 48 ] have demonstrated a 36 fold higher ICs in human VL subjects. In our present study, we observed almost 5 fold higher ICs in human PKDL subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, distinct seven bands were found to be glycoprotein in nature as demonstrated by PAS silver double stain and lectin blot ( Fig 3D , Fig 4B ). Notably, the 162 kDa, 109 kDa, 70 kDa MW CIC protein bands have similar MW as glycoproteins found on amastigotes and promastigotes of Leishmania donovani [ 60 ], whereas other protein bands like 61 kDa, 55 kDa, 45 kDa and 37 kDa had MW similar to those found in Leishmania antigen [ 48 ]. All the above mentioned seven protein bands were present in immunoblot ( Fig 4A ).…”
Section: Discussionmentioning
confidence: 99%
“…Its diagnosis is accomplished by molecular and/or conventional parasitological techniques, as well as by immunological assays. However, accurate diagnosis depends on the current clinical status and immune response of the infected hosts, with falsenegative and/or false-positive results being frequently Section Editor: Sarah Hendrickx encountered (Sakkas et al 2016;Jamal et al 2017;Van Griensven and Diro 2019).…”
Section: Introductionmentioning
confidence: 99%